Nicotine Enhances Staphylococcus epidermidis Biofilm Formation by Altering the Bacterial Autolysis, Extracellular DNA Releasing, and Polysaccharide Intercellular Adhesin Production - Wu, Yang; Ma, Yue; Xu, Tao; Zhang, Qing-zhao; Bai, Jinna; Wang, Jiaxue; Zhu, Tao; Lou, Qiang; Götz, Friedrich; Qu, Di; Zheng, Chun-quan; Zhao, Ke-qing (Frontiers in Microbiology, 2018)
Staphylococcus epidermidis is a common bacterial colonizer of human skin and mucous membranes, yet it has emerged as an important nosocomial pathogen largely due to its ability to form biofilms. Tobacco smoke has been demonstrated as a contributor to various infection diseases by improving the biofilm formation of multiple bacterial species; however, the association between tobacco smoke and S. epidermidis biofilm is still unclear. In this study, we tested the effect of nicotine, one of the most active components of tobacco, on S. epidermidis biofilm formation, and we studied the underlying mechanisms. Our results showed that nicotine promoted the biofilm formation of S. epidermidis 1457 strain (SE1457) and enhanced its initial attachment to a polyethylene surface as well as polysaccharide intercellular adhesin (PIA) production. In addition, an increased extracellular DNA release and a higher autolysis rate of SE1457 was detected after nicotine treatment, which was consistent with the increased ratio of dead cells in nicotine-treated SE1457 biofilm observed with confocal laser-scanning microscopy. Furthermore, the effect of nicotine on several autolysis-related and biofilm-related gene knockout mutants of SE1457 was tested. It showed that in △saeRS, △lytSR and △sceD, nicotine induced increase in biofilm formation was similar to that in SE1457; but in △arlRS, △atlE and △icaC, the effect was obviously impaired. Consistently, the increase of the bacterial autolysis rate in arlRS and atlE induced by nicotine was not as significant as that in SE1457. Meanwhile, the growth inhibition of nicotine on SE1457 was observed, and it was much less on arlRS and restored by the arlRS complementation. The arlRS transcription in SE1457 was inhibited by nicotine during cultivation as indicated by a promoter reporter assay using green fluoresent protein. Taken together, our study indicates that nicotine improves S. epidermidis biofilm formation by promoting its initial attachment and intercellular accumulation; the arlRS, atlE, and ica genes mediating bacterial autolysis and PIA production play an important role in this process.